ANALISIS PENGARUH AUDIT TENURE, AUDIT LAG, OPINION SHOPPING, LIQUIDITY, LEVERAGE DAN DEBT DEFAULT TERHADAP PENGUNGKAPAN OPINI AUDIT GOING CONCERN - Ibrahim Rabbani; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2021)
This study aimed to examine the effect of audit tenure, audit lag, opinion shopping, liquidity, leverage and debt default on the auditor's disclosure of going concern opinion. This study used secondary data taken from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique used purposive sampling method, there were 409 observations that had met the predetermined sample criteria. This study uses logistic regression to test the hypothesis. The results showed that the audit lag and leverage had a positive effect on going concern opinion, and the liquidity had a negative effect on going concern opinion. Meanwhile, audit tenure, opinion shopping debt default did not have a negative effect on going concern opinion.